STRATEGI 4P DAN PRAKTEK PEMASARAN DIGITAL DALAM PRODUK JAMUR CRISPY DI KABUPATEN KEDIRI - Rasyadan Taufiq Probojati; M. Daimul Abror; Reksa Nanda Prayoga; Wardatul Chamro’ (Jurnal Abdi Masyarakat, 2025)
Efforts to increase the added value of fresh mushroom products by turning them into crispy mushrooms carried out by Kebon Jamur partners face obstacles related to meeting market standards and marketing. In this digital era, the community service team sees a great opportunity to help increase product sales and effective and efficient marketing, while also helping the surrounding community's economy. Through a participatory approach from the planning stage with FGD, it was decided to conduct training on the 4P digital marketing strategy. The training consisted of material and practice sessions attended by 50 participants. The training results showed an increase in participants' knowledge, skills, and attitudes, with an average score of 79%. This means that the training successfully improved the capacity of the 4P digital marketing strategy.